Improving learning and accountability in foreign aid. (January 2020) - Clements, Paul
Highlights: A significant body of evidence suggests that evaluations of foreign aid projects are often positively biased. Learning and accountability particularly at portfolio level depend on consistent measures of impacts and cost effectiveness. The currently dominant evaluation approach in foreign aid, based on the DAC criteria, makes consistent measures less likely. An evaluation association could establish and defend standards and conventions for estimating impacts and cost effectiveness. The paper illustrates strengths, weaknesses, and possible improvements with examples from several health projects. Abstract: Learning and accountability in foreign aid require project comparisons, but the dominant framework for aid evaluation institutionalizes inconsistency. Today, most aid evaluations are organized in terms of the Development Assistance Committee (DAC) criteria: relevance, effectiveness, efficiency, impact and sustainability. Usually the evaluators determine how to apply each criterion. Also, with donor agencies organizing their own evaluation systems, project monitoring tends to be weak and many evaluations are superficial, positively biased, and/or poorly timed. Logically, the most effective way to improve learning and accountability would be to implement independent and consistent evaluation for cost effectiveness. We substantiate and illustrate this argument by explaining why evaluation should be oriented to cost effectiveness and how this could be accomplished by an evaluation association, and by discussing six evaluations of health projects and several documents that summarize many evaluations. The proposed association would provide a stronger foundation in evidence and incentive environment for aid managers to make decisions that maximize the cost effectiveness of their interventions. This would enhance the professionalism of foreign aid and hasten an end to poverty.